The bones of paris ebook - King, Laurie R. (Harris Stuyvesant, 2013)
NAMED ONE OF THE BEST BOOKS OF THE YEAR BY THE SACRAMENTO BEE New York Times bestselling author Laurie R. King, beloved for her acclaimed Mary Russell/Sherlock Holmes series, consistently writes richly detailed and thoroughly suspenseful novels that bring a distant time and place to brilliant life. Now, in this thrilling new book, King leads readers into the vibrant and sensual Paris of the Jazz Age—and reveals the darkest secrets of its denizens.   Paris, France: September 1929. For Harris Stuyvesant, the assignment is a private investigator’s dream—he’s getting paid to prowl the cafés and bars of Montparnasse, looking for a pretty young woman. The American agent has a healthy appreciation for la vie de bohème, despite having worked for years at the U.S. Bureau of Investigation. The missing person in question is Philippa Crosby, a twenty-two year old from Boston who has been living in Paris, modeling and acting. Her family became alarmed when she stopped all communications, and Stuyvesant agreed to track her down. He wholly expects to find her in the arms of some up-and-coming artist, perhaps experimenting with the decadent lifestyle that is suddenly available on every rue and boulevard .   As Stuyvesant follows Philippa’s trail through the expatriate community of artists and writers, he finds that she is known to many of its famous—and infamous—inhabitants, from Shakespeare and Company’s Sylvia Beach to Ernest Hemingway to the Surrealist photographer Man Ray. But when the evidence leads Stuyvesant to the Théâtre du Grand-Guignol in Montmartre, his investigation takes a sharp, disturbing turn. At the Grand-Guignol, murder, insanity, and sexual perversion are all staged to shocking, brutal effect: depravity as art, savage human nature on stage.   Soon it becomes clear that one missing girl is a drop in the bucket. Here, amid the glittering lights of the cabarets, hides a monster whose artistic coup de grâce is to be rendered in blood. And Stuyvesant will have to descend into the darkest depths of perversion to find a killer . . . sifting through The Bones of Paris . BONUS: This edition includes an excerpt from Laurie R. King's Dreaming Spies. Praise for The Bones of Paris   “Haunting . . .  a portrait of the City of Light that glows with the fires of Hell.” —Richmond Times-Dispatch   “A compelling thriller . . . complex, more than a little kinky, and absolutely fascinating.” — Booklist (starred review)   “Highly entertaining . . . Laurie R. King perfectly captures [the Jazz Age] as she explores the City of Light’s avenues and alleys.” —The Denver Post   “Engrossing . . . Readers who enjoy Laurie R. King’s noteworthy Mary Russell/Sherlock Holmes mystery series are in for a surprise.” — BookPage   “A chilling mystery and a haunting love letter to the Paris of Hemingway’s Lost Generation.” —Library Journal